IMPROVING THE METHODOLOGY OF IDENTIFYING AND MANAGEMENT OF RISKS AFFECTING THE ACTIVITIES OF COMMERCIAL BANKS - SHERMATOV, G’OFURJON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Improvement of risk management mechanisms in commercial banks is of particular importance. Because risks are characterized by different levels of risk depending on the type. In this article, the essence of the concept of banking risks, their causes, types, and the issues of its identification, prevention and minimization are explained theoretically and practically.